DEVELOPING A FUNCTIONAL DEFINITION OF SMALL-SCALE FISHERIES IN SUPPORT OF MARINE CAPTURE FISHERIES MANAGEMENT IN INDONESIA - Halim, Abdul; Wiryawan, Budy; Loneragan, Neil R.; Hordyk, Adrian; Sondita, M. Fedi A.; White, Alan T.; Koeshendrajana, Sonny; Ruchimat, Toni; Pomeroy, Robert S.; Yuni, Christiana (JFMR (Journal of Fisheries and Marine Research), 2020)
Small-scale capture ï¬sheries have a very important place globally, but unfortunately are still mostly unregulated. Typically, they are deï¬ned based on capture ï¬sheries characteristics, technical attributes of ï¬shing vessels, and socio-economic attributes of ï¬shers. Indonesia uses the term â€˜small-scale ï¬sherâ€™ (nelayan kecil), currently deï¬ned to include ï¬shing boats of â‰¤ 10 gross tons (GT), which previously covered only boats of â‰¤ 5 GT. Because small-scale ï¬shers are by law granted a privilege by government to be exempted from ï¬sheries management measures (e.g. ï¬sheries licensing system), its current deï¬nition jeopardizes ï¬sheries sustainability and signiï¬cantly increases the size of unregulated and unreported ï¬sheries. It is also unfair, as it legitimizes the payment of government support to relatively well-oï¬€ ï¬shers. This paper aims to develop a functional deï¬nition of small-scale ï¬sheries (perikanan skala kecil) to guide policy implementation to improve capture ï¬sheries management in Indonesia. A deï¬nition of small-scale ï¬sheries is proposed as a ï¬sheries operation, managed at the household level, ï¬shing with or without a ï¬shing boat of < 5 GT, and using ï¬shing gear that is operated by manpower alone. This deï¬nition combines attributes of the ï¬shing vessel (GT), the ï¬shing gear (mechanization), and the unit of business decision making (household) to minimize unregulated and unreported ï¬shing and focus government aid on people who are truly poor and vulnerable to social and economic shocks. The terms small-scale ï¬sheries and small-scale ï¬shers must be legally diï¬€erentiated as the former relates to ï¬sheries management and the latter relates to empowerment of marginalized ï¬shers.